Platelet Count Predicts Adverse Clinical Outcomes After Ischemic Stroke or TIA: Subgroup Analysis of CNSR II - Yang, Ming; Pan, Yuesong; Li, Zixiao; Yan, Hongyi; Zhao, Xingquan; Liu, Liping; Jing, Jing; Meng, Xia; Wang, Yilong; Wang, Yongjun (Frontiers in Neurology, 2019)
Background: The clinical significance of platelet count (PC) for ischemic cerebrovascular disease is not well established and further risk stratification according to baseline PC within normal range has not been reported before. We aim to evaluate the prognostic effect of baseline circulating PC within normal range on the risk of long-term recurrent stroke, mortality and functional outcomes after ischemic stroke or TIA. Methods: We derived data of eligible patients with ischemic stroke or TIA from the China National Stroke Registry (CNSR) II. Subjects were divided into quintiles according to baseline PC within normal range (100-450×109/L). Multivariable cox regression and logistic regression were adopted to explore the correlation of baseline PC with recurrent stroke, mortality and poor functional outcomes (modified Rankin Scale 3 6) within one-year follow-up. Results: Among the16842 eligible subjects, the average age was 64.7±11.9, 1241(7.4%) had recurrent stroke, 1377(8.2%) died and 3557(21.1%) ended up with poor functional outcomes after one-year follow-up. Compared with the third PC quintile (186-212×109/L), patients in the top quintile (249-450×109/L) presented with increased risk of recurrent stroke (adjusted hazard ratio 1.21, [1.02-1.45]), all-cause mortality (adjusted hazard ratio 1.43, [1.19-1.73]) and poor functional outcome (adjusted odds ratio 1.49, [1.28-1.74]), while patients in the lowest PC quintile(100-155×109/L) undertook higher risk of poor functional outcome (adjusted odds ratio 1.19, [1.02-1.38]). Conclusion: In ischemic stroke or TIA patients with platelet count within normal range, platelet count may be a qualified predictor for long-term recurrent stroke, mortality and poor functional outcome.